THE EFFECTIVENESS OF Eucheuma cottonii EXTRACT AGAINST DENGUE VECTOR LARVAE AS AN EVALUATION FOR NATURAL LARVICIDE DEVELOPMENT - Setyaningrum, Endah; Novrianda, Nabila Tias; Mumtazah, Dzul Fithria; Rosa, Emantis (BRIN Publishing (Penerbit BRIN), 2025)
Dengue fever (DHF) is a tropical disease transmitted by the Aedes aegypti mosquito. Prolonged use of synthetic chemical larvicides such as Abate® has led to resistance and environmental impacts. Therefore, an alternative natural larvicide that is more environmentally sustainable is needed. Eucheuma cottonii is a red alga known to contain bioactive compounds such as flavonoids, alkaloids, terpenoids, saponins, and tannins that can potentially inhibit mosquito larvae development. This study aims to evaluate the effectiveness of the ethanol extract of E. cottonii on the mortality of Aedes aegypti instar III larvae as a basis for the development of natural biolarvicides. The study used a completely randomized design (CRD) with six treatments: four extract concentrations (50 ppm, 100 ppm, 200 ppm, and 300 ppm), one positive control (Abate®), and one negative control (water). Each test unit contained 20 third-instar larvae with four replicates. Observations were made 4, 8, 24, 48, and 72 hours after treatment. The highest larval mortality was achieved at a 200 ppm concentration of 13.25 ± 3.94. The LC₅₀ value at 24 hours was 42.35 ppm, while the LT₅₀ reached 52.77 hours, indicating a slow and less effective larvicidal effect at the test concentration. Although the ethanol extract of E. cottonii contains bioactive compounds, its effectiveness as a larvicide against Aedes aegypti larvae is still relatively low. These results indicate that E. cottonii is not optimally used alone as a bio-larvicide, but still has the potential to be further developed through improved extraction methods, increased concentrations, or combination formulations. This study provides a foundation for creating sustainable and environmentally friendly plant-based larvicides.